Investigating the Use of Polypropylene in Hot Mix Asphalt on the Mix Design of Flexible Pavements - Robert Kainerugaba (Uganda Christian University, 2024)
Roads are of flexible pavement type and made with a wearing course consisting of bitumen as the binder, fillers, and aggregates. The purpose of this study was to examine the impact of polypropylene use in hot mix asphalt on the longevity of flexible pavements. The bulk density, penetration test, softening point test, aggregate crushing value, aggregate impact value, ten percent fines value, and tensile strength tests carried out to determine the mechanical properties of the materials. The Marshall Mix design, then used to determine the optimal binder content, and the indirect tensile strength, Marshall Stability, and flow were used to assess the mix's strength and durability in addition to the volumetric analysis of the mix design. Optimum Polypropylene mix addition of 1.5%, Stability increased, VMB increased, VMA value reduced, Air voids value reduced, Flow increased, ITS value increased. This shows a positive impact from the addition of Polypropylene in the mix design, which enhances the adhesive and cohesive properties of the asphalt concrete hence improving the Strength and durability properties of hot mix asphalt since the. This study or Research should be carried out to determine the behavior or impact of Polypropylene on AC14 properties.